Induction of Quercus ilex L. haploid and doubled-haploid embryos from anther cultures by temperature-stress (SILVAE GENETICA, 2013)
This paper describes a method to obtain haploid and doubled-haploid (DH) embryos using anther cultures of holm oak (Quercus ilex L.). The production of haploids and DH through gametic embryogenesis provides an attractive biotechnological tool for developing homozygous lines from heterozygous parents, which is important in breeding programs, as well as in genetic studies. As a consequence, protocols to produce homozygous plants have a significant impact on forest tree improvement. Anthers were subjected to different temperature treatments for embryo induction: a cold pre-treatment (4 C) from 3 to 7 days was carried out at the beginning, followed by a heat shock (33 C) from 2 to 5 days. Most anthers responding to these stress treatments contained vacuolated microspores, indicating that this developmental stage is responsive to embryogenesis induction in holm-oak microspores. In all cases, embryos grew from the interior of the anthers, breaking through the degenerating anther walls. Under these conditions, embryo formation occurred in 31 anthers between 46 and 95 days after culture initiation. Embryo analysis performed with flow-cytometry and DNA-microsatellite markers showed haploid profiles and/or spontaneous doubling of the chromosomes during early regeneration stages. This is, to our knowledge, the first published report on gametic embryogenesis in holm oak.

CLONACIÓN DE PROGENIES DE ALCORNOQUES PLUS DE CUATRO REGIONES DE PROCEDENCIA MEDIANTE EMBRIOGÉNESIS SOMÁTICA PARA LA OBTENCIÓN DE MATERIALES FORESTALES DE REPRODUCCIÓN (IV Congreso Forestal Español, 2005)
Se ha realizado una selección fenotípica individual de árboles plus de alcornoque en los rodales selectos establecidos por el Instituto del Corcho, la Madera y el Carbón Vegetal (ICMC, Junta de Extremadura) en cuatro regiones de procedencia: Montes de Toledo-Villuercas, Sierra Morena Occidental, Sierra de San Pedro, y Norte de Cáceres-Salamanca. De los árboles seleccionados se han recogieron estaquillas en primavera de 2002 y 2003, y bellotas inmaduras durante el verano de 2002, 2003 y 2004. De las estaquillas se establecieron inicialmente 48 clones mediante cultivo de yemas axilares (MANZANERA y PARDOS, 1990). La elevada edad de los árboles hizo imposible la estabilización y mantenimiento de los cultivos y actualmente sólo sobrevive 1 de los clones. De los embriones cigóticos inmaduros, según protocolo de BUENO et al. (1992), se consiguió inducir embriogénesis somática en los 55 árboles muestreados de los 61 seleccionados. Estas líneas son regularmente subcultivadas, y los embriones obtenidos madurados, germinados y aclimatados para el establecimiento de ensayos de progenie con propósito de disponer de materiales de mejora. En enero de 2005 se estableció la primera finca de ensayo y actualmente se dispone de 1400 vitroplantas más para el establecimiento de nuevas parcelas. Palabras

Cytological analysis of early microspore divisions leading to gametic embryo formation in Quercus suber L. anther cultures (Acta Physiologiae Plantarum, 2005)
The cor re la tion be tween the phenologic stage of the in flo res - cence and the microspore de vel op ment stage was stud ied. Cyto log i cal ex am i na tions of the de vel op ment of micro spores dur - ing in vi tro an ther cul ture of cork oak (Quercus suber L.), were car ried out dur ing the first four weeks of cul ture. To ob serve the di vi sion oc cur ring in the micro spores, an thers were taken ran domly from the cultures after heat shock treatment and were stained with DAPI. Most of the an thers re spond ing to a heat stress treat ment con tained 91 % vacuolated micro spores, in di cat ing that this de vel op men tal stage is re spon sive to embryo genesis in duc tion in cork-oak micro spores. Af ter the heat shock treat ment some cork-oak micro spores were in duced and ini ti ated the embryogenic path way with the oc cur rence of nu mer ous sym met ric mi to sis, pro duc ing struc tures with two to ten or more nu clei. These lead to the for ma tion of high num - bers of multicellular cork-oak micro spores (pro-em bryos). Twenty-forty days af ter in duc tion, small white glob u lar and cotyledonal em bryos were ob served, which fur ther de vel oped root and shoot, re gen er at ing plantlets.

SSR Markers for Quercus suber Tree Identification and Embryo Analysis (Journal of Heredity, 2001)
Three Quercus simple sequence repeat (SSR) markers were amplified by polymerase chain reaction (PCR) from nuclear DNA extracts of trees and in vitro-induced haploid embryos from anther cultures of Quercus suber L. These markers were sufficiently polymorphic to identify 10 of 12 trees located in two Spanish natural areas. The same loci have been analyzed in anther-derived haploid embryos showing the parental tree allele segregation. All the alleles were present in the haploid progeny. The presence of diverse alleles in embryos derived from the same anther demonstrated that they were induced on multiple microspores or pollen grains and they were not clonally propagated. Also, diploid cultures and mixtures of haploid-diploid tissues were obtained. The origin of such cultures, either somatic or gametic, was elucidated by SSR markers. All the embryos showed only one allele, corroborating a haploid origin. Allelic composition of the haploid progeny permitted parental identification among all analyzed trees.
10.1093/jhered/92.3.292

Embriogénesis gamética para obtención de haploides en alcornoque. (II Congreso Forestal Español, 1997)
Inducción of haploid embryos and regeneration of plantlets have been obtained for the first time, in cork oak (Quercus suber L.) by combining a starvation treatment in anther culture with a mild heat shock at 33°C for 5 days, followed by culture at 25°C in a simple agar medium without growth regulator.s. The same conditions had been shown previously to be optimal for embryogenic induction in isolated microspore cultures of several model species such as tobacco and wheat. These results support the notion that stress, particularly sucrose starvation, a heat shock or a combination of both treatments could be the major and general signal responsible for the inhibition of normal gametophytic development of the microspores and for the induction of the alternative embryogenic pathway. A similar approach may be used for the production of haploid and doubled haploids for plant breeding in other species that like most forest trees, are still recalcitrant in anther culture.

Micropropagation of juvenile and adult Quercus suber L. (Plant Cell, Tissue and Organ Culture, 1990)
This paper describes research on the application of tissue culture techniques to the micropropagation of cork oak (Quercus suber L.), a forest species of ecological and industrial importance in the Mediterranean area. Apical buds and nodal stem segments were employed as initial explants. Their origins were young seedlings, stump sprouts and sprouts formed on cuttings collected from old trees. The action of the mineral medium and growth regulators was studied in the multiplication stage. Media with low concentrations of ions, such as Sommer's or Heller's, are more suitable for growth and proliferation of explants than other media richer in salts. It was also observed that cytokinin (BA) must be present for the culture development. Adding low concentrations of auxin (NAA) to the medium improves the multi- plication rate, especially in vegetative material of adult origin. The auxin type is the most important factor in the promotion of rhizogenesis. The method of application determines the quality of the root system. Treatment with low concentrations of IBA added to the rooting medium gives the best results. High sucrose concentration also improves rooting. Diluting the mineral rooting medium is slightly favourable, although there is no significant difference between it and the standard mineral concentration.